(untitled) (Comprehensive Journal of Science, 2025)
The development of speaking skills represents a central objective in English as a Foreign Language (EFL) education, particularly within higher education contexts where communicative competence is essential for academic success and professional engagement. Speaking is not merely the production of language; rather, it involves the dynamic integration of grammatical knowledge, lexical resources, pronunciation accuracy, and discourse management within real-time interaction (Harmer, 2001). Despite its importance, speaking remains one of the most challenging skills for EFL learners, especially in contexts where exposure to authentic language use is limited. Within the Libyan educational system, English language instruction has historically emphasized grammar, reading, and translation. This tradition has contributed to the development of receptive knowledge; however, it has not adequately supported the development of productive skills, particularly speaking. At the University of Benghazi – Al-Abyar Branch, many students demonstrate a noticeable gap between their knowledge of English and their ability to use the language effectively in spoken communication. This gap raises concerns regarding the effectiveness of current teaching practices and the extent to which they align with contemporary approaches to language instruction. Several contextual factors contribute to this issue. Limited exposure to English outside the classroom restricts opportunities for meaningful practice, while large class sizes reduce the likelihood of individual participation. In addition, teacher-centered instructional approaches continue to dominate many classrooms, where the focus remains on content delivery rather than student interaction. These conditions create an environment in which learners become passive recipients of knowledge rather than active participants in communication. Communicative Language Teaching (CLT) has been widely promoted as an effective approach to address such challenges. CLT emphasizes the use of language for meaningful communication and encourages interaction through tasks such as discussions, role plays, and collaborative activities (Richards, 2008). However, the implementation of CLT in the Libyan context has often been partial or inconsistent, limiting its potential impact on students’ speaking development. This study seeks to investigate the current state of speaking instruction at the University of Benghazi – Al-Abyar Branch by exploring students’ experiences, challenges, and perceptions. Through qualitative inquiry, the study aims to provide a deeper understanding of the factors influencing speaking development and to identify pedagogical practices that can enhance oral proficiency among Libyan EFL learners.